PENGARUH PERLAKUAN MEDIA TANAM, DOSIS ZEOLIT DAN KCl TERHADAP LAJU INFEKSI PATHOGEN Ganoderma boninense DI PEMBIBITAN UTAMA KELAPA SAWIT (Elaeis guineensis Jacq) VARIETAS D X P PPKS - Guntoro Guntoro; Marshal Arifin Sinaga; Windra Surono (Jurnal Agro Estate, 2017)
Rotten disease of the base of the stem is currently already attacked crops of oil palm in the nursery. This last Task done research in the area of Sekolah Tinggi Ilmu Pertanian Agrobisnis Perkebunan. The research using random Design Group (RAK) Factorial with the sum of 12 and Deuteronomy 3 x as much treatment, oil palm seedlings grown in Sterile soil with polibeg media and ex Ganoderma with the awarding of the Zeolite and KCl application. Testing parameters are arranged on the test Range with Fingerprints Analysis F.Observations on the treatment of planting Media against the number of leaves showed no effect. For the application of Zeolite in General does not give a real Influence on the entire parameters. Whereas for the application of KCl test result statistics gives a real for influence is evident against the number of leaves, stem diameter, and height of the plant. The highest number of leaf chlorophyll contained in T0Z0K2 treatment with 66.49 CCI. The level of Infection Pathogens disease Ganoderma boninense, the level of the lowest root damage is present on the T0Z1K2 treatment with 31.62%.